Kinerja pertumbuhan ikan Patin Pangasius sp. yang diberi sinbiotik di kolam tanah stagnan, Bukit Tunggal, Palangka Raya - Ricky Djauhari; Shinta Sylvia Monalisa (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2019)
Combination supplementation of probiotic Saccharomyces cerevisiae and MOS prebiotic applications on a laboratory scale had been performed and was able to improve survival rate, growth and immune response of Pangasius sp. against multiple pathogens. The purpose of this research was to test the effects of combination probiotic Saccharomyces cerevisiae and MOS prebiotic administration on growth performance of Pangasius sp. reared in ponds (net cages 1x1x1 m3) on field scale. Fish with initial average weight 2-3 g that has been reared for 30 days was reared in fish pond in stocking density of 80 fishes/m2. This research consisted of two treatments with three replications: K treatment (without synbiotic administration) and P treatment (administration of probiotic Saccharomyces cerevisiae and MOS prebiotic for each 0.2%). The results showed that synbiotic administration was able to improve the survival rate, daily growth rate, feed conversion ratio, feed efficiency and weight gain of Pangasius sp. Keywords : Synbiotic, Pangasius sp., growth performance